2022
DOI: 10.1038/s41598-022-12240-2
|View full text |Cite|
|
Sign up to set email alerts
|

Low divergent MeV-class proton beam with micrometer source size driven by a few-cycle laser pulse

Abstract: Spatial characterization of 0.5 MeV proton beam, driven by 12 fs, 35 mJ, 1019 W/cm2 intense laser-foil interaction is presented. The accelerated proton beam has been applied to obtain a high-resolution, point-projection static radiograph of a fine mesh using a CR-39 plate. The reconstruction of mesh edge blurring and particle ray tracing suggests that these protons have an effective source size (FWHM) of just 3.3 ± 0.3 µm. Furthermore, the spatial distribution of the proton beam recorded on the CR-39 showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…where δR p depends on the pinhole size [18,23,38]. The overall energy resolution for the total analyzed energy range, i.e., from a few keV up to 100 MeV, slightly decreases, as expected in the case of the linear gradient.…”
Section: Optimized Design For Proton Spectrum With 100 Mev Cut-off En...supporting
confidence: 58%
See 1 more Smart Citation
“…where δR p depends on the pinhole size [18,23,38]. The overall energy resolution for the total analyzed energy range, i.e., from a few keV up to 100 MeV, slightly decreases, as expected in the case of the linear gradient.…”
Section: Optimized Design For Proton Spectrum With 100 Mev Cut-off En...supporting
confidence: 58%
“…In Section 4.1, we have shown that a higher energy spectral range can be achieved, without significant losses in terms of energy resolution. This "new" detectable low proton energy range is particularly relevant for applications, such as the ones in cultural heritage [39,40], laser driven proton boron fusion [41,42] and towards the perspective of low divergent MeV-class proton beam with micrometer source size driven by a few-cycle laser pulse [38]. The minimum detectable proton energy value, for the TP geometry that we are proposing, becomes 0.38 MeV.…”
Section: Discussionmentioning
confidence: 81%
“…one shot per 30 min at the PALS facility, as described in references 26,27 ). On the other hand, implementation of kHz sources of laseraccelerated protons has recently been reported [39][40][41][42] . However, to the best of our knowledge, repetitive laser-driven alpha particle sources have never been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…From the measured number of particles in the ion spectra (figures 3(b), (d), and 4(b)) and the measured divergence of the proton beam of 5 • (see [38]), one can derive the spectral energy content in the proton beam. The assumption that the divergence of the proton beam is the same for all target thicknesses is rather conservative as the proton beam divergence may increase as the target thickness decreases.…”
Section: Conversion Efficiencymentioning
confidence: 99%